The Effects of Family Culture and Marital Decisions of the Business Owners on Access to Financing of Very Small Businesses: A Study in the North West Region of Cameroon - Wirkom, Stanley Kongnyuy; Jumbo, Urie Eleazar; Kueda, Berthelo Wamba (Business Perspective Review, 2024)
Purpose: This study seeks to examine the effects of family culture (presence during family meetings, assistance in important family events, and strong family bonds) as well as marital decisions (mutual participation, joint savings decisions, and joint ventures) on access to financing of very small businesses in the North West Region of Cameroon. Methods: The study used a series of exogenous and control variables adapted from the model of Gikonyo, Agwata, & Anyango (2011) who proposed a strategic model for quantitative research. Primary data were collected through convenient sampling from 293 very small business owners in each divisional headquarters of the North West Region of Cameroon. We used the multiple correspondence analysis to construct indexes for family culture, marital decisions as well as access to financing of very small businesses. The hypotheses of the study were then tested using the ordinary least square estimation technique. Results: The results obtained showed in aggregate, a positive and significant effect of family culture and marital decisions on access to financing. More precisely, the coefficients of presence during family meetings, assistance in important family events as well as strong family bonds are positive. These results were statistically significant at 1% level. Implications: This study has significant practical implications on the financial health of very small businesses in the context of developing countries like Cameroon in general and the North West Region of Cameroon in particular plagued by the crisis and COVID-19. The study therefore concluded that if very small business owners can improve on the respect of family cultures and can jointly decide on their financial actions with their spouses, they will have better access to financing, especially in developing countries like Cameroon and more particularly in the North West Region of the country.